Secure and Energy Efficient Routing in Wireless Multi-hop Clustered Networks Based on RSSI - Gupta, Jatin; Kathuria, Anchal; Sengupta, Jyotsna (International Journal of Engineering and Technology, 2018)
Today is an era of technology and computing. This technological revolution has created a need for anything and everything to be connected to each other in order to achieve a better communication and utilisation of resources. An isolated computer becomes an information island and may not be able to achieve the optimum use of power and resources. To connect computer systems, there are two options available: one is the installation of LAN (local area networking) cables which may be cumbersome at first but it ensures security and the other one is wireless media. Wireless networking, apart from being simple and efficient, poses serious challenges of security breach by rogue nodes and compromise in performance due to dynamic nature of mobile nodes. Extensive research has been carried out so far and several algorithms and protocols have been formulated to incorporate the location and energy aware characteristics for routing. The technique proposed in this paper considers various factors like energy, distance, vulnerability and battery power while propagating the packet information between the nodes in a sensor networks implementing the heterogeneity in terms of nodes. The ultimate aim is to enhance the longevity of the sensor network while ensuring the security of the network. This is achieved by considering RSSI (Received Signal Strength Indicator) factor in accord with other factors in a multi-hop routing. Extensive simulation results and analysis demonstrate that the proposed technique outperforms other security mechanisms and protocols in the literature in terms of energy awareness, security and routing efficiency.